Handbook of carbon, graphite, diamond, and fullerenes properties, processing, and applications - Pierson, Hugh O. (Noyes Publications, 1993)
This book is a review of the science and technology of the element carbon and its allotropes: graphite, diamond and the fullerenes. This field has expanded greatly in the last three decades stimulated by many major discoveries such as carbon fibers, low-pressure diamond and the fullerenes. These carbon materials are very different in structure and properties. Some are very old (charcoal), others new (the fullerenes). They have different applications and markets and are produced by different segments of the industry.
Keywords: Carbon.; elektronické knihy; electronic books